2020
DOI: 10.36103/ijas.v51i4.1081
|View full text |Cite
|
Sign up to set email alerts
|

Models to Predict Slope Length From Other Watershed Attributes

Abstract: Soil erosion by water is an extensive and increasing problem worldwide. Albeit, this problem has been recognized as a significant hazard in Iraq, yet the number of studies on this topic is very limited. Most of the models used for estimating soil erosion contain parameters for slope length factor (LS). A major constraint is the difficulty in extracting the LS factor. Accordingly, the current study was initiated with the main objective of deriving models to predict the slope length from relatively easy to measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The length of overland flow (L g ), expressed in kilometers, is the length of water running on the surface before it joins the mainstream, which affects the drainage basin's hydrologic and physiographic development [22]. Overland flow length can be and was calculated using Eq.1 from [25]. Infiltration and percolation occurring in the soil, both of which vary in time and place, have a considerable influence on L g [47].…”
Section: Length Of Overland Flow (L G )mentioning
confidence: 99%
“…The length of overland flow (L g ), expressed in kilometers, is the length of water running on the surface before it joins the mainstream, which affects the drainage basin's hydrologic and physiographic development [22]. Overland flow length can be and was calculated using Eq.1 from [25]. Infiltration and percolation occurring in the soil, both of which vary in time and place, have a considerable influence on L g [47].…”
Section: Length Of Overland Flow (L G )mentioning
confidence: 99%
“…The Erbil plain located to the southern part of the mountainous area, is characterized by having a high potential for agricultural production in case of water availability. Dry farming is practiced on a large scale over this plain, wheat, barley are the principal winter crops [15]. Keya and Karim [16] reported that the models derived for spatial events are region specific and cannot be generalized outside its region without calibration or validation.…”
Section: Introductionmentioning
confidence: 99%